“Migrant Struggles”, A new Framework for the Collective Action Sociology of Social Movements (Andamios, Revista de Investigación Social, 2015)
This paper proposes to consider the migrant struggles as a new field in sociology that ponders over the collective action. This work is an exercise that focuses on struggles led by migrants with or without legal documents. Thus, this emerging social movement can be deciphered. Also, the main actors, practices and normative or political projects of these struggles, as well as the exact role they play on the map of current dissent, are analyzed.
Keywords: Migrants; social movements; agency; social movement sociology; migrant’s struggles